2016
DOI: 10.1108/mbe-12-2015-0059
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital, impact factor on competitiveness: manufacturing industry SMEs in Mexico

Abstract: Purpose The main purpose of this paper is to analyse the impact of the intellectual capital (IC) on the competitiveness in the manufacturing small- and medium-sized enterprises (SMEs) in Mexico. Design/methodology/approach The approach of this investigation is developing a theoretical construct to determine the correlation between IC and competitiveness and find the most relevant factors that impact it, where IC is independent variable and the competitiveness is dependant variable. Using the Likert scale to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…For instance, IC is the core driver to stand up firms from other firms in a competitive and challenges environment (Jordão & Almeida, 2017; Kamukama, 2013; Kamukama et al, 2011). Studies in this nature have argued that IC has significantly and positively contributed to firms' success and performance (Sanchez‐Gutierrez, Mejia‐Trejo, Vargas‐Barraza, & Vazquez‐Avila, 2016; Wang, Lu, Kweh, & Lai, 2014). However, it is argued that little intellectual capabilities are not sufficient to gain CA.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, IC is the core driver to stand up firms from other firms in a competitive and challenges environment (Jordão & Almeida, 2017; Kamukama, 2013; Kamukama et al, 2011). Studies in this nature have argued that IC has significantly and positively contributed to firms' success and performance (Sanchez‐Gutierrez, Mejia‐Trejo, Vargas‐Barraza, & Vazquez‐Avila, 2016; Wang, Lu, Kweh, & Lai, 2014). However, it is argued that little intellectual capabilities are not sufficient to gain CA.…”
Section: Introductionmentioning
confidence: 99%
“…Sanchez-Gutierrez et al (2016) found that IC directly influences the competitiveness of manufacturing small and medium-sized enterprises (SMEs) in Mexico. Based on data from three countries (i.e.…”
mentioning
confidence: 99%
“…This research allows us to support a number of researches carried out in Mexico that have analysed the relationship between intellectual capital and organisational performance (Heredia and González, 2010;Mejía et al, 2014;De la Garza et al, 2015;Sánchez-Gutiérrez et al, 2016;Ibarra-Cisneros and Hernandez-Perlines, 2018). The conclusions are heterogeneous, but by and large, they conclude the existence of this relation in different sectors of the economy and in a particular way, with certain dimensions of IC.…”
Section: Discussionmentioning
confidence: 60%